KEAJAIBAN HARI TUHAN: TAFSIR KITAB MALEAKHI 4:1-6 - Pondi, Diva Yostina (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2024)
Abstract : The prophecy of Malachi 4:1-6 contains important eschatological themes surrounding the day of the Lord and its implications for believers. This article aims to explore the theological meaning behind this prophecy. With an analytical approach to Bible interpretation and qualitative methods by collecting data from literature such as books, journals and the Bible. The goal is to gain a deep understanding of the topic being researched, namely the concept of the day of the Lord and eschatological elements such as Divine judgment, the salvation of the redeemed, and the reality of the Kingdom of God. The concept of the "day of the Lord" refers to a future moment in which God will dramatically intervene in history, judge sin, and provide salvation for His redeemed people. After the dark phase of judgment, the dawn of victory and salvation arises for God's people. Transgressors are punished, while God's redeemed people are freed, healed, protected, and win the battle. It reflects the eternal reality of God's kingdom fulfilled at the coming of the "day of the Lord." As a result, Malachi 4:1-6 provides a deep understanding of God's plan in salvation history and its fulfillment in the coming of Christ. This understanding is important to strengthen the faith of believers in the midst of this era.Keywords: day of the Lord, eschatology, Malachi, Kingdom of GodAbstrak : Nubuatan Maleakhi 4:1-6 mengandung tema-tema eskatologis penting seputar hari Tuhan dan implikasinya bagi umat percaya. Tulisan ini bertujuan mengeksplorasi makna teologis di balik nubuatan tersebut. Dengan pendekatan analisis tafsir Alkitab dan metode kualitatif dengan mengumpulkan data dari literatur seperti buku, jurnal, dan Alkitab. Tujuannya adalah untuk mendapatkan pemahaman yang mendalam tentang topik yang sedang diteliti, yaitu konsep hari Tuhan dan unsur-unsur eskatologis seperti penghakiman Ilahi, keselamatan umat tebusan, serta realitas Kerajaan Allah. Konsep "hari Tuhan" merujuk pada momen masa depan di mana Allah akan secara dramatis campur tangan dalam sejarah, menghakimi dosa, dan memberikan keselamatan bagi umat-Nya yang ditebus. Setelah fase penghakiman yang gelap, terbitlah fajar kemenangan dan keselamatan bagi umat Tuhan. Para pelanggar dihukum, sementara umat yang ditebus oleh Tuhan dibebaskan, disembuhkan, dilindungi, dan memenangkan pertarungan. Ini mencerminkan realitas kekal dari kerajaan Allah yang tergenapi pada saat kedatangan "hari Tuhan." Hasilnya, Maleakhi 4:1-6 memberi pemahaman mendalam tentang rencana Allah dalam sejarah keselamatan dan penggenapannya pada kedatangan Kristus kelak. Pemahaman ini penting untuk menguatkan iman umat percaya di tengah zaman.Kata kunci: hari Tuhan, eskatologi, Maleakhi, Kerajaan Allah